CURRENT ISSUES OF NEWBORN CARE IN SURGICAL DISEASES - T. U. Bykovskaya; M. A. Shishov (Медицинский вестник Юга России, 2015)
Purpose: to identify the trigger group nosology in newborns, acting on which it is possible to reduce infant mortality and to assess the links between the development of complications and the period from birth to transfer to the surgical ward in congenital intestinal obstruction due to atresia of the intestinal tube.Materials and methods: the structure of the post-mortem diagnosis of infants with surgical diseases of the fi veear period, as well as medical cards of 95 infants with atresia of the intestinal tube with a favorable outcome of treatment.Results: one of the trigger groups are congenital malformations, accompanied by obstruction of the digestive tract; a statistically signifi cantly higher incidence of complications such as postoperative pneumonia in infants with atresia of the small intestine and rectum high atresia transferred to the surgical ward aft er 24 hours of birth.Summary: to reduce the infant mortality rate is necessary, including, establish regulatory requirements for a transfer to a children’s hospital surgical neonates with atresia of the small intestine and colon atresia highest within the fi rst 24 hours of birth.